(untitled) (Patan Pragya, 2020)
This paper discusses on the emigrated Newars from Kathmandu Valley to different parts of Solududhkunda Municipality. The paper explores the origin and migration of the Newars and tries to analyze how the emigrated Newars united each other; and socially and culturally adapted throughsocial organizations such as guthi and samaj. The nature of this paper is qualitative. Semi structured interviews, group discussions and key informants’ interviews were the major tools for data collection. The genealogies of the Newars were reviewed to analyze their out-migration process. However, the causes of their out-migration from the Kathmandu Valley was not clear buttrade, kinship, forced migration and local disputes may be the probable causes of their outmigration. The establishments of guthi or samaj are very much important to the Newars to adjust inthe new socio-cultural environments. The guthi or samaj not only fulfilled their socio-cultural and economic needs but also showed their joint strength and power to cope with other caste and ethnic groups. Giving membership to non-Newar families and attending Buddhists ceremonies as stakeholders, accepting Hindu Brahmin as their priest and acculturation are the adapting strategies of the Newars in the new circumstances. However, remigration of the educated and capable Newaryouths is the major questions for their existence in the Solu-dudhkunda Municipality.